Altered Inhibitory Mechanisms in Parkinson’s Disease: Evidence From Lexical Decision and Simple Reaction Time Tasks - Letanneux, Alban; Velay, Jean-Luc; Viallet, François; Pinto, Serge (Frontiers in Human Neuroscience, 2021)
Introduction Although the motor signs of Parkinson’s disease (PD) are well deﬁned, nonmotor symptoms, including higher-level language deficits, have also been shown to be frequent in patients with PD. In the present study, we used a lexical decision task to find out whether access to the mental lexicon is impaired in patients with PD, and whether task performance is affected by bradykinesia. Materials and Methods Participants were 34 nondemented patients with PD, either without (off) medication (n = 16) or under optimum (on) medication (n = 18). A total of 19 age-matched control volunteers were also recruited. We recorded reaction times to the lexical decision task and a simple reaction time (control) task. In each task, stimuli were either visual or auditory. Statistical analyses consisted of repeated-measures analyses of variance and Tukey’s HSD post hoc tests. Results In the lexical decision task, participants with PD both off and on medication exhibited intact access to the mental lexicon in both modalities. In the visual modality, patients off medication were just as fast as controls when identifying real words, but slower when identifying pseudowords. In the visual modality of the control task, reaction times for pseudowords were significantly longer for PD patients off medication than for controls, revealing an unexpected but significant lexicality effect in patients that was not observed in the auditory modality. Performances of patients on medication did not differ from those of age-matched controls. Discussion Motor execution was not slowed in patients with PD either off or on medication, in comparison with controls. Regarding lexical access, patients off medication seemed to (1) have difficulty inhibiting a cognitive linguistic process (i.e., reading) when it was not required (simple reaction time task), and (2) exhibit a specific pseudoword processing deficit in the lexical decision task, which may have been related to impaired lateral word inhibition within the mental lexicon. These deficits seemed to be compensated by medication.